Déficit de atención como consecuencia de la hiperactividad en los estudiantes de tercer año básico de la Escuela de Educación Básica 6 de Octubre del cantón Urdaneta, Provincia de Los Ríos - Mosquera Cañar, Angy Madian (2019)
Attention deficit hyperactivity disorder (ADHD) is a chronic disorder that affects millions of children; often, it continues in adulthood. ADHD involves a combination of persistent problems, such as difficulty maintaining attention, hyperactivity, and impulsive behaviors. It is possible that the child with ADHD also deals with low self-esteem, problematic relationships and poor performance at school. Sometimes, the symptoms diminish as the child grows. However, some people never completely overcome the symptoms of ADHD. Anyway, they can learn strategies to succeed. Although the treatment will not cure ADHD, it can be very helpful in overcoming the symptoms. The treatment typically includes medications and behavioral interventions. If it is diagnosed and treated early, the result can be much better.